Preparation, Spectroscopy, Physicochemical Properties and X-ray Structure Analysis of 3,4,5-Trimethoxy N(2-hydroxybenzylidene) aniline - Kodjo Charles Guillaume; Zabri Herve; Benie Anoubile; Estienne Jacques (E-Journal of Chemistry)
3,4,5-Trimethoxy N-(salicylidene) aniline was synthesized and characterized by IR spectroscopy, 1H NMR and x-ray single crystal analysis. UV-visible spectroscopy was used for physicochemical tests. X-ray data reveals that the crystalline network cohesion of this compound is essentially assured by CH/pi type hydrogen bounds. It crystallized in the orthorhombic Pbcn space group. Electronic spectroscopy shows that the title compound doesn't present photochromic property but thermochromic one. Intermolecular interactions analysis confirms for this compound a thermochromic structural predisposition.